Correlations between selected characteristics that describe body trunk and feet in children and young people aged 4 to 18 years - Marek Sokołowski; Mirosław Mrozkowiak (Kazimierz Wielki University, 2017)
Abstract Introduction. Few studies have documented the measurements of selected characteristics of body posture and examination of their mutual relationships, mainly due to the limited capabilities of the diagnostic methods used. Material and Method. The examinations conducted in the group of children and young people age 4 to 18 years allowed for recording 18229 observations and values of 92 characteristics that describe body trunk and feet. The measurement of selected characteristics of body posture was based on the photogrammetric method. Conclusion The statistical analysis of the significance of correlations between the characteristics of feet and body trunk in all age groups demonstrated that, as expected, the most substantial and most frequent correlations can be observed at the age of 7 to 13 years, slightly lower at the age of 14 to 18 years, and the lowest at the age of 4 to 6 years. It should also be noted that although the first age range does not show any significant correlations with morphological characteristics of feet (length and width), they are observed in two other ranges. With regard to sexual dimorphism at the age of 4 to 6 years, more numerous and more frequent correlations are observed in boys compared to girls, with these proportions being similar (with slight advantage of boys) at the age of 7 to 13 years. In the last range (14 to 18 years), as expected, girls demonstrate substantially more numerous and more frequent correlations compared to boys. With regard to the environmental dimorphism at the age of 4 to 6 years, there is not disproportion in the number of characteristics, with the frequency of significant correlations being insignificantly greater in boys. In the group of children and young people aged 7 to 13 years, participants from urban areas showed greater advantage in both the number and frequency of correlations with the characteristics of body trunk. In the last analysed age range (14 to 18 years), mutual qualitative and frequency disproportions start to disappear, becoming similar to the pattern observed at the age of 4 to 6 years. Streszczenie Wstęp. Pomiary wybranych cech postawy ciała i badanie ich wzajemnych związków było rzadko podejmowane między innymi ze względu na możliwości stosowanych metod diagnostycznych. Materiał i metoda. Przeprowadzone badania w grupie dzieci i młodzieży w wieku od 4 do 18 lat, pozwoliły zarejestrować 18229 obserwacji, wielkości 92 cech opisujących tułów i stopy. Do pomiaru wybranych cech postawy ciała zastosowano metodę fotogrametryczną. Podsumowanie Przedstawiona analiza statystyczna istotności związków cech stóp z cechami tułowia we wszystkich grupach wiekowych wykazała, że najliczniejsze i o największej częstości występują w wieku 7 - 13 lat, nieco mniejsze w 14-18 lat i najmniejsze w wieku 4-6 lat, co było zgodnie z oczekiwaniami. Należy także zauważyć, że o ile w pierwszy przedziale wieku nie ma istotnych związków z cechami morfologicznymi stóp (długość, szerokość), to w pozostałych dwóch już występują. W zakresie dymorfizmu płciowego w wieku 4-6 lat zachodzą znacząco liczniejsze i częstsze związki wśród chłopców niż dziewcząt, w wieku 7-13 lat dysproporcje wyrównują się, ale chłopcy nadal zachowują nieco większą przewagę. W ostatnim przedziale 14-18 lat, dziewczęta wykazują zdecydowanie liczniejsze i częstsze związki wśród niż chłopcy, co także było zgodne z oczekiwaniami. W zakresie dymorfizmu środowiskowego w wieku 4-6 lat nie ma dysproporcji w ilości cech, a częstość istotnych związków jest nieznacznie większa u chłopców. Natomiast w przedziale 7-13 lat osobnicy ze środowiska miejskiego wykazują bardzo dużą przewagę tak w ilości jak i częstości związków z cechami tułowia. W ostatnim analizowanym przedziale wieku, 14-18 lat, wzajemne dysproporcje ilościowe i częstości zacierają się, zbliżając do sytuacji występującej w wieku 4-6 lat.